Ubumba olungashi : a case study of South African artist Hezekiel Ntuli’s unfired ceramics - McGinn, Isabelle (University of Pretoria, 2024)
Mini Dissertation (MSocSci (Heritage and Cultural Sciences) Heritage Conservation)--University of Pretoria, 2023.